Analysis of Students' Anxiety Level in Facing the Final Biology Examination at SMA Negeri 1 Kota Sungai Penuh - Sapriani, Ema Tri; Ferry, Dharma; Kencanawati, Indah (Bioilmi: Jurnal Pendidikan, 2024)
Anxiety is a condition where there is excessive worry, resulting in difficulty in controlling the problems being faced. This study aims to analyze the level of student anxiety in facing the biology final exam for students at SMAN 1 Sungai Penuh in class XI for the 2023/2024 academic year. The method used in this research is quantitative with the research population consisting of class. The research sample was selected using simple random sampling technique consisting of 162 students. Data was collected using a student anxiety level questionnaire. The results showed that the average score for men was 47.679 and the average score for female was 47.679. The results of this analysis indicate that almost all students in class XI at this school feel anxious when taking the biology final exam. This illustrates how crucial the active involvement of teachers is in supporting students' emotional well-being. By being actively involved, teachers can be creating a learning environment that supports the development of all students.